Advances in injectable in situ-forming hydrogels for intratumoral treatment - Shin, Gi Ru; Kim, Hee Eun; Kim, Jae Ho; Choi, Sangdun; Kim, Moon Suk (Pharmaceutics, 2021)
Chemotherapy has been linked to a variety of severe side effects, and the bioavailability of current chemotherapeutic agents is generally low, which decreases their effectiveness. Therefore, there is an ongoing effort to develop drug delivery systems to increase the bioavailability of these agents and minimize their side effects. Among these, intratumoral injections using in situ-forming hydrogels can improve drugs’ bioavailability and minimize drugs’ accumulation in non-target organs or tissues. This review describes different types of injectable in situ-forming hydrogels and their intratumoral injection for cancer treatment, after which we discuss the antitumor effects of intratumoral injection of drug-loaded hydrogels. This review concludes with perspectives on the future applicability of, and challenges for, the adoption of this drug delivery technology.
Keywords: Anticancer effect; Cancer; Injectable in situ-forming hydrogel; Intratumoral injection